2007
DOI: 10.1080/15228053.2007.10856111
|View full text |Cite
|
Sign up to set email alerts
|

E-Commerce Adoption in Small Businesses: Cases from New Zealand

Abstract: Electronic commerce (EC) adoption in small to medium-sized enterprises (SMEs) is confronted with diferent diflculties. This is due to reasons relating to the SME's structure and to their surrounding environment. This research is interested in identifying factors influencing EC adoption and success in SMEs. A review of the technological innovation adoption (TIA) research in SMEs provides useful insights into factors influencing adoption. Thus, this research attempted to achieve two main objectives. Initially, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 41 publications
(39 reference statements)
2
17
0
Order By: Relevance
“…A literature review of ICT adoption was conducted to identify the constructs within TOE framework,. Al-Qirim (2007) found the relationship between complexity, compatibility, top-management support, and innovation adoption to be significant. This is true, while it found that the relationship between Information Systems (IS) expertise, trialability and innovation adoption as insignificant, a belief in congruence with other studies (Mirchandani and Motwani 2001;Huang et al 2008).…”
Section: Acceptancementioning
confidence: 94%
“…A literature review of ICT adoption was conducted to identify the constructs within TOE framework,. Al-Qirim (2007) found the relationship between complexity, compatibility, top-management support, and innovation adoption to be significant. This is true, while it found that the relationship between Information Systems (IS) expertise, trialability and innovation adoption as insignificant, a belief in congruence with other studies (Mirchandani and Motwani 2001;Huang et al 2008).…”
Section: Acceptancementioning
confidence: 94%
“…Furthermore, many other studies found that relative advantages had also a positive and significant impact on e‐commerce adoption (Abou‐Shouk, Megicks, & Lim, ; El‐Gohary, ; Ghobakhloo et al, ). Moreover, Al‐Qirim ( ) found that technological innovation factors such as relative advantage, complexity and compatibility as well as organizational factors and individual factors affect the adoption of e‐commerce among SMEs in New Zealand.…”
Section: Technology Organization and Environment Factors And B2b E‐mentioning
confidence: 99%
“…There are also a number of studies that proved that the enterprise size is one of the factors that lead to the adoption of new technologies. The studies of: El‐Gohary ( ), Al‐Qirim ( ), Lal ( ), and Lertwongsatien and Wongpinunwatana ( ) are examples of such studies. El‐Gohary ( ), for example, found that firm size had a significant and positive effect on e‐marketing adoption by Egyptian small tourism organizations.…”
Section: Organizational Factorsmentioning
confidence: 99%
“…The internal/external technologies connected to the firm describe the technological context; the descriptive attributes of the firm describe the organizational context and environmental characteristics include the industry, competitors, suppliers and government (Jain, Le, Lin, & Cheng, 2011). Our research examines the influence of complexity, compatibility, and trialability in technological context (Doolin & Al Haj Ali, 2008;Lin & Lin, 2008;Mirchandani & Motwani, 2001;Premkumar & Roberts, 1999;Ramdani, Kawalek, & Lorenzo, 2009;Roberts & Pick, 2004;Srinivasan, Lilien, & Rangaswamy, 2002;Zhu, Kraemer, & Xu, 2003); top management support, perceived financial cost and BIM expertise in organizational context (Al-Qirim, 2007;Balocco, Mogre, & Toletti, 2009;Doolin & Al Haj Ali, 2008;Grover, 1993;Huang, Janz, & Frolick, 2008;Kuan & Chau, 2001;Lin & Lin, 2008;Moore & Benbasat, 1991;Premkumar & Roberts, 1999;Zhu & Kraemer, 2005); and client requirements and trade partner readiness in environmental context (Al-Qirim, 2007;Doolin & Al Haj Ali, 2008;Lin & Lin, 2008;Premkumar & Roberts, 1999;Ramdani et al, 2009;Zhu et al, 2003) Adoption and Figure 2: TOE Framework (Tornatzky & Fleischer, 1990) In the current research, TOE framework has been used for investigating the factors affecting BIM adoption among architectural firms in India. As BIM processes require organization wide adoption (including adoption in the project delivery network) and as this research focuses on studying the BIM adoption among architecture firms (and not individuals) an organizational-level adoption theory is deemed suitable for the current research.…”
Section: Technology-organization-environment (Toe) Frameworkmentioning
confidence: 99%